3D Carbon Foam Supported Edge‐Rich N‐Doped MoS2 Nanoflakes for Enhanced Electrocatalytic Hydrogen Evolution. Issue 18 (21st January 2020) - Jia, Xueying; Ren, Hongyuan; Hu, Hanbin; Song, Yu‐Fei
Abstract: Molybdenum disulfide (MoS2 ) is one of the most promising alternatives to the Pt‐based electrocatalysts for the hydrogen evolution reaction (HER). However, its performance is currently limited by insufficient active edge sites and poor electron transport. Hence, enormous efforts have been devoted to constructing more active edge sites and improving conductivity to obtain enhanced electrocatalytic performance. Herein, the 3D carbon foam (denoted as CF) supported edge‐rich N‐doped MoS2 nanoflakes were successfully fabricated by using the commercially available polyurethane foam (PU) as the 3D substrate and PMo12 O40 3− clusters (denoted as PMo12 ) as the Mo source through redox polymerization, followed by sulfurization. Owing to the uniform distribution of nanoscale Mo sources and 3D carbon foam substrate, the as‐prepared MoS2 ‐CF composite possessed well‐exposed active edge sites and enhanced electrical conductivity. Systematic investigation demonstrated that the MoS2 ‐CF composite showed high HER performance with a low overpotential of 92 mV in 1.0 m KOH and 155 mV in 0.5 m H2 SO4 at a current density of 10 mA cm −2 . This work offers a new pathway for the rational design of MoS2 ‐based HER electrocatalysts. Abstract : More active sites ! An edge‐rich 3D MoS2 ‐CF (CF=carbon foam) composite was successfully fabricated, and it exhibited high electrocatalytic performance with low overpotential ( η 10(basic) =92, η 10(acidic) =155 mV) for the hydrogen evolution reaction (HER) in both alkaline and acidic media.